Green Synthesis of Tin Oxide Nanoparticles using Psidium guajava Leaves Extract and its Applications in Antibacterial and Antioxidant Activities - Binadi, Tirtha Raj; Mishra, Paramatma; Poudel, Bhoj Raj; Gautam, Surendra K (Journal of Nepal Chemical Society, 2025)
In this study, tin oxide (SnO2) nanoparticles was synthesized via green synthetic route using Psidium guajava (Guava) leaf extract as reducing, capping and stabilizing agents. The synthesized SnO2 NPs were characterized by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR) and UV-visible spectroscopy. The XRD analysis revealed that synthesized SnO2 nanoparticles have tetragonal rutile structure, and the particle size was found to be 19.5 nm estimated by using Debye-Scherer’s equation. In addition, the average particle size calculated by using Williamson-Hall plot method was found to be 21.5 nm. The FTIR spectra reveals hydroxyl, alkyl, alkane, amide and hydroxyl tin group as a functional group. UV-Visible absorption spectra were found to be 270 nm, and its corresponding band gap energy was found to be 3.88 eV. Moreover, the antimicrobial activities of different concentrations of SnO2 NPs using Psidium guajava leaf extract were also tested. Accordingly, the result showed that the highest zone of inhibitions was measured for SnO2 NPs using 30mg/mL solution concentration and observed to be 18mm, 21mm and 20mm for S. aereus, P. aeruginosa and K. pneumoniae respectively. As synthesized SnO2 NPs also showed significant antioxidant efficacy against 2,2-diphenyl-1-picrylhydrazyl radical.